AKAD MUDHARABAH MUTHLAQAH PADA PRODUK DEPOSITO DI BANK SYARIAH MANDIRI CAPEM SITUBONDO - Subaidi; Subyanto (Al-Hukmi : Jurnal Hukum Ekonomi Syariah dan Keluarga Islam, 2020)
Bank Syariah Mandiri branch office Situbondo applies mudharabah muthlaqah agreement for deposit products because it is very interesting for customers. They handed over mudharabah saving management absolutely to Bank Syariah Mandiri, without limits either in types of investment, period of time, or business sector. However it must does not be contrary to Islamic principles. Islam invites wealthy persons to develop and invest their assets. Instead Islam forbids them from concealing their wealth. Likewise, Islam also forbids them from hoarding their wealth. Of course, the money can be used for useful projects that have positive impact such as creating labour market and improving economic activity. Keywords : ,,